2019
DOI: 10.22190/fupes190409011u
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obesity on Schoolgirls Motor Skill Performance

Abstract: The aim of this study is to compare the motor skills status of girls with different nutritional status. The research sample consisted of 180 girls aged 10 and was divided into 4 subsamples: malnourished, normally nourished, pre-obese and obese girls. The assessment of the motor space was carried out with a battery of eighteen motor tests. The identification of the differences between the groups was carried out by the Univariate Analysis of Variance (ANOVA) method. The significance of the differences between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Similar results, specifically on sideways jumping, push-ups and a 6-min run, were reported, all requiring movement of the body through space or against gravity [12]. A study on 10-year-old girls divided into malnourished, normally nourished, pre-obese and obese groups also found that obese girls struggled significantly more with motor tests requiring quick movements of the entire body over long distances or power-based movements, including running speed, repetitive strength and explosive power of the lower extremities [32].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results, specifically on sideways jumping, push-ups and a 6-min run, were reported, all requiring movement of the body through space or against gravity [12]. A study on 10-year-old girls divided into malnourished, normally nourished, pre-obese and obese groups also found that obese girls struggled significantly more with motor tests requiring quick movements of the entire body over long distances or power-based movements, including running speed, repetitive strength and explosive power of the lower extremities [32].…”
Section: Discussionmentioning
confidence: 99%
“…They spend too much time in a sedentary position, usually in front of a computer screen or watching TV (Joshi, Cole, & Overton, 2016). Weakening of motor abilities increases hypokinesia that leads to obesity; obesity endangers health, and moreover fosters motor inefficiency; this leads to the spiral of causative events that endanger public health (Uzunović et al, 2019). The above negative behaviours noted in society lead to changes in body composition which increase the prevalence of overweight and obesity and to a decrease in physical fitness followed by disorders of the musculoskeletal system (Gosh & Bouchard, 2017;Jakičić, & Otto, 2006;Podstawski, 2013;Saczuk, Wasiluk, Wilczewski, & Wilczewski, 2016).…”
Section: Introductionmentioning
confidence: 99%